Marginal ulcers and associated risk factors after Roux-en-Y gastric bypass. Issue 2 (4th March 2023) - Wynn, Matthew; Tecson, Kristen M.; Provost, David
Abstract: As the prevalence of morbid obesity continues to climb in America, so does the popularity of the Roux-en-Y gastric bypass (RYGB) to achieve weight loss goals; however, a long-term risk of RYGB is marginal ulceration, which requires urgent surgery if perforated. We sought to identify characteristics associated with elective vs urgent presentation for marginal ulcer following RYGB. Retrospective data for consecutive cases with marginal ulcers that required surgical intervention from May 2016 to February 2021 were queried from our institution's bariatric database, and differences in patient characteristics and clinical course were assessed according to presentation. Forty-three patients underwent surgery for marginal ulcer during the study timeframe. Twenty-four (56%) patients presented electively and were treated with resection of the gastroenterostomy and reanastomosis; the remaining 19 (44%) presented urgently with perforation and were treated with omental patch repair. Demographics, comorbidities, and medications were similar between groups. Patients with urgent presentations were less likely to have bleeds (0% vs. 33%, P = 0.0056) and strictures (16% vs. 46%, P = 0.0368), but were more likely to require admission to the intensive care unit (32% vs. 4%, P = 0.0325) and have a longer median length of stay (2 vs. 5 days, P < 0.0001). Bariatric surgeons must properly counsel patients about the risk of marginal ulcer development to prevent dangerous perforation, intensive care unit stays, and long hospitalizations.